59.8k views
0 votes
Easy - lots of points!!
For the function f defined by f(x) = 2x^2 – 3x, evaluate: f(x+3)

User P Kuijpers
by
4.6k points

2 Answers

1 vote
Answer: f(5) = 14 should be the answer
User Enrico Giurin
by
5.3k points
2 votes

Answer:

2x² + 9x + 9

Explanation:

To evaluate f(x + 3) substitute x = x + 3 into f(x), that is

f(x + 3) = 2(x + 3)² - 3(x + 3) ← expand (x + 3)² using FOIL

= 2(x² + 6x + 9) - 3(x + 3) ← distribute both parenthesis

= 2x² + 12x + 18 - 3x - 9 ← collect like terms

= 2x² + 9x + 9

User Unn
by
4.9k points